Influenza Vaccination Coverage and Influencing Factors in Type 2 Diabetes in Mainland China: A Systematic Review and Meta-Analysis - Cheng Yang; Shijun Liu; Jue Xu; Wen Fu; Xin Qiu; Caixia Jiang (Vaccines)
Background: Influenza has many harmful effects on people with type 2 diabetes mellitus (T2DM), such as hyperglycemia and increasing incidence of cardiovascular and cerebrovascular diseases. Epidemiological evidence shows that influenza vaccinations can effectively prevent deterioration in T2DM patients. At present, there is a lack of nationwide studies on the vaccination status of influenza vaccines for patients with certain chronic diseases. This study aimed to evaluate the influenza vaccination status of T2DM patients in mainland China and the factors affecting their influenza vaccination. Methods: Data were sourced from PubMed, Embase, Web of Science, the China Biology Medicine Disc (CBMdisc), the China National Knowledge Infrastructure (CNKI), and the Wanfang Database. The keywords used in the literature search included “diabetes”, “diabetes mellitus”, “DM”, “diabetic”, “T2DM”, “influenza vaccine”, “flu vaccine”, “China”, and “Chinese”. A total of 249 articles were retrieved through the searches; 7 articles met the inclusion criteria. The fixed-effects model was used when heterogeneity was low and a random-effects model was used when the heterogeneity was high. Results: The influenza vaccination coverage rate was 1.46% in diabetic patients and 9.99% in elderly diabetic patients. The influenza vaccination rate of type 2 diabetes patients with a high education level is higher than that of patients with a low education level. (OR: 1.462 [1.123, 1.903]). Meanwhile, gender (OR: 1.076, 95%CI: 0.893–1.295), marriage (OR: 1.283; 95%CI: 0.931–1.766), and occupation (OR: 1.049; 95% CI: 4.422–2.606) have no significant impact on influenza vaccination in patients with type 2 diabetes. Conclusions: This study found that the coverage of influenza vaccination in patients with T2DM in Chinese mainland was low, and there were few relevant research articles. In China’s mainland areas, education background is an important factor affecting the influenza vaccination of T2DM patients. China should continue to improve the influenza vaccination rate of patients with type 2 diabetes.